Structurally modified tetrabromophthalic-based compounds as an anti-corrosion agent in microbial influenced saline systems - Vignesh, Krishnan; Sujithra, Sankar; Vajjiravel, Murugesan; Santhosh, Selvakumar; Narenkumar, Jayaraman; AlSalhi, Mohamad S.; Devanesan, Sandhanasamy; Arunkumar, Paulraj; Rajasekar, Aruliah; Malik, Tabarak (Frontiers in Materials, 2025)
This study investigates the efficacy of synthesized corrosion inhibitors and evaluates them for microbial influenced corrosion (MIC) control in carbon steel API 5LX80 induced by Pseudomonas aeruginosa in 3.5 wt% NaCl. Tetrabromophthalic-based inhibitors (TBIs) have been synthesised and ascertained on the basis of spectral measurements determined by Fourier transform infrared spectroscopy (FTIR) and systematically evaluated for MIC. The results showed that this TBI effectively reduced biofilm formation at 200 ppm. FTIR and X-ray diffraction (XRD) observations confirmed that adsorption of a protective film over the surface of metal inhibited bacterial growth. FTIR analysis revealed the adhesion of the inhibitor over the metal surface. Polarization studies indicated that this inhibitor 1 decreased the corrosion current densities (1.4588 × 10−4A/cm2) by a mixed-mode mechanism (both anodic and cathodic) and exhibited 75% corrosion inhibition efficiency. Thus, the present investigation has gained significance in reporting about novel corrosion inhibitors possessing biocidal activity to control MIC in API 5LX80 carbon steel used in oil and pipeline transporting properties.